If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + (-4) = 2x + 8 4x + -4 = 2x + 8 Reorder the terms: -4 + 4x = 2x + 8 Reorder the terms: -4 + 4x = 8 + 2x Solving -4 + 4x = 8 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -4 + 4x + -2x = 8 + 2x + -2x Combine like terms: 4x + -2x = 2x -4 + 2x = 8 + 2x + -2x Combine like terms: 2x + -2x = 0 -4 + 2x = 8 + 0 -4 + 2x = 8 Add '4' to each side of the equation. -4 + 4 + 2x = 8 + 4 Combine like terms: -4 + 4 = 0 0 + 2x = 8 + 4 2x = 8 + 4 Combine like terms: 8 + 4 = 12 2x = 12 Divide each side by '2'. x = 6 Simplifying x = 6
| 2g+5+2g= | | 7y=81-24 | | 9w-4+2w+9-5w=41 | | (x)(X+1)=145 | | 17×r/2=34 | | 7/8(3/5x) | | (x+1)*(x-2+1)=24 | | X^2+X-145=0 | | (x+3)(x+4)=x^2+7x+12 | | 2x=(-2)x | | X-10+x+2x+13=88 | | y=2.3x+5.4 | | -6(v+3)+3v+7=6v+7 | | 2a-(a+3)+3= | | 2(v+8)+5v=37 | | 9=5(u-3)+3u | | 28=4(w+6)-6w | | 1/9a=6 | | 6(-2-x)=-5(x+3) | | 5x-4-3x=14 | | -4=n | | 4e^3x+2=110 | | 10(s-4)=-132 | | 4e^3x+2=20 | | 10(s-4)=3 | | 10/3(10) | | 4e^3x-2=110 | | 2/3=7/x-4 | | -7-15x=23 | | 0.2+x=3 | | 2x+3y+6z=98 | | 60x=-32 |